Music Practices Across Borders : (E)Valuating Space, Diversity and Exchange - Peres da Silva, Glaucia; Hondros, Konstantin (2019)
Long description: Connecting migration studies and the theory of valuation, this collection offers an interdisciplinary approach to the study of transnational music practices. Conceiving music as a practice not confined to audibility, the contributions reveal how music emerges in concrete situations through people, objects, techniques, meanings, and emotions in different parts of the world and during different historic periods. Values are thereby created and shared, and creative processes are evaluated in terms of diversity, space and exchange.This book presents cases of contemporary, popular and traditional music, festivals and trade fairs, albums and band projects, shedding light on the tensions between the transfer, reconstruction and creation of music in different contexts. - Biographical note: Glaucia Peres da Silva (Dr.) works as assistant professor at the Institute of Sociology at the University of Duisburg-Essen. Her research focuses on global markets and music.Konstantin Hondros works as a research associate at the Institute of Sociology at the University of Duisburg-Essen. His research focuses on evaluation, music, and copyright.